Image and Policy: The case of Turks and Pomaks in inter-war Bulgaria, 1918-44 (with special reference to education) - Mančeva, Mila (Islam and Christian-Muslim relations, 2001)
The article aims to reconstruct the public image of Turks in Bulgaria as it is presented by Bulgarian public figures and state officials and to study the influence of their perceptions of Muslim minorities on the formation of state policies. It argues that the prevailing images of 'otherness' and the paternalistic attitudes of suspicion and fear among Bulgarian governmental and administrative officials have enforced and been reinforced by concrete policy measures at local and central levels. The article traces the relation between recommended and real policy measures in the sphere of minority education as an indicator of state-minority relations in the inter-war period.